Seduced by second chances - Ryan, Reese (Harlequin desire, 2019)
Gideon Johns inspired singer Jessie Humphrey to write her first hit about unrequited love. So when a star-studded event brings Jessie face-to-face with her former crush, sparks fly. But the handsome-as-ever real estate billionaire is still her sister<U+2019>s ex. Still off-limits. Still impossible to resist. Is she setting herself up for more heartache, or for her wildest fantasy come true?